Pelatihan Pembuatan Kue Lapis Kacang sebagai Strategi Meningkatkan Hard Skill Kewirausahaan Mahasiswa (Indonesian Version) - Florensia Florensia; Anggit Dyah Kusumastuti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
As a method to enhance students' entrepreneurial skills, peanut layer cake production training was implemented. This training approach directly combines theory and practice to improve students’ understanding and technical abilities. The training was conducted with five participants and consisted of three stages. The initial session included a pretest and basic entrepreneurship material, the core session involved hands-on practice in making peanut layer cake, and the closing session consisted of evaluation and a posttest. The results showed a significant improvement in students' understanding of entrepreneurship, with an average increase of 35 points from their pre-training scores. After the training, students' interest in entering the culinary business also increased. The findings indicate that peanut layer cake production training is effective in fostering entrepreneurial spirit and enhancing students’ technical skills. It is recommended that universities conduct more practice-based training to help students develop into entrepreneurs in the Society 5.0 era.